Programa educativo aprendizaje servicio para la mejora de la formación ciudadana en estudiantes de la I.E.P.S Sagrado Corazón Iquitos 2024 - Rengifo Lopez, Sarhinaa Cathyuska (2025)
The research aimed to evaluate the effect of implementing an educational program based on the service-learning methodology to improve civic education in students at I.E.P.S. Sagrado Corazón, Iquitos, during the year 2024. The study adopted an evaluative, longitudinal, univariate, and field design, with a sample of 63 students divided into two groups: experimental (31 students) and control (32 students). The data collection technique was the survey, complemented by a written performance test, an instrument validated by experts in the field. The results demonstrate a significant improvement in the civic education of the experimental group students after the intervention. At baseline, both groups showed comparable levels, with 90.6% of students in the control group at the deficient level and 64.5% in the experimental group. After the program’s implementation, the experimental group experienced substantial progress, achieving 100% of students at the very good level, highlighting the program’s effectiveness in enhancing civic competencies. These findings validate the general hypothesis and emphasize the transformative potential of the service-learning methodology as a pedagogical tool in the studied context.